1995
DOI: 10.1101/gad.9.8.995
|View full text |Cite
|
Sign up to set email alerts
|

Assembly and function of a TCR alpha enhancer complex is dependent on LEF-1-induced DNA bending and multiple protein-protein interactions.

Abstract: In this study we examine the molecular basis for the synergistic regulation of the minimal TCRa enhancer by multiple proteins. We find that reconstitution of TCRc~ enhancer function in nonlymphoid cells requires expression of the lymphoid-specific proteins LEF-1, Ets-1 and PEBP2a (CBFc~I, and a specific arrangement of their binding sites in the enhancer. We show that Ets-1 cooperates with PEBP2a to bind adjacent sites at one end of the enhancer, forming a ternary complex that is unstable by itself. Stable occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
502
2
5

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 524 publications
(535 citation statements)
references
References 69 publications
(95 reference statements)
26
502
2
5
Order By: Relevance
“…Among the ets family, ETS1 mRNA was known to be localized in the bone tissue (Kola et al, 1993). The signi®cance of the interaction between runt family and ets family has been reported (Giese et al, 1995;Wotton et al, 1994). PEBP2aA, ETS1 and DNA were reported to form a ternary complex and have a synergistic e ect on transactivation of the T cell receptor b gene, in which runt and ets binding sites are juxtaposed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the ets family, ETS1 mRNA was known to be localized in the bone tissue (Kola et al, 1993). The signi®cance of the interaction between runt family and ets family has been reported (Giese et al, 1995;Wotton et al, 1994). PEBP2aA, ETS1 and DNA were reported to form a ternary complex and have a synergistic e ect on transactivation of the T cell receptor b gene, in which runt and ets binding sites are juxtaposed.…”
Section: Discussionmentioning
confidence: 99%
“…PEBP2a speci®cally recognizes a consensus sequence, PuACCPuCA and has been reported to control polyoma virus enhancer (Kamachi et al, 1990), murine leukemia virus enhancers , T cell-speci®c genes (Giese et al, 1995;Hallberg et al, 1992;Hsiang et al, 1993;Prosser et al, 1992;Redondo et al, 1992), enzymes (myeloperoxidase, neutrophil elastase, granzyme B serine protease) (Nuchprayoon et al, 1994;Wargnier et al, 1995) and cytokines and their receptors (GM-CSF, IL3, CSF-1) (Cameron et al, 1994;Frank et al, 1995;Zhang et al, 1994). PEBP2aA and ETS1 have been shown to bind together and interact synergistically on the promoter of the T cell receptor a gene (Giese et al, 1995) and T cell receptor b gene (Wotton et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Thus this observation taking together with the mapping of the Erg domains responsible for the homodimerization shows that the ETS domain serves a key dual function, DNA-binding and in protein ± protein interactions. It is also the case for other transcriptional factors, for example, the Runt family proteins are able to physically interact with other factors via their RUNT domain, also responsible of DNA-binding properties (Ogawa et al, 1993;Giese et al, 1995).…”
Section: Negative In¯uence Of the Central Domain (Cd) Of Erg Proteinsmentioning
confidence: 99%
“…Several Ets factors interact with other regulators of gene expression and cell cycle progression. Ets-1 binds various transcription factors, including Sp1 (Gegonne et al, 1993), PEBP2a/AML-1 (Giese et al, 1995), GHF-1/Pit-1 (Bradford et al, 1995), MafB (Sieweke et al, 1996), NF-kB, AP-1 (Thomas et al, 1997), and USF-1 (Sieweke et al, 1998). Despite its high degree of structural similarity with Ets-1, only one protein-protein interaction between Ets-2 and p300/CBP (Jayaraman et al, 1999) and two transcriptional cooperations with GATA3 (Blumenthal et al, 1999) or ATF/Jun family members (Cirillo et al, 1999) have been reported.…”
Section: Introductionmentioning
confidence: 99%